(untitled) (Veterinária Notícias, 2020)
Bovine mastitis is the most frequent disease in dairy herds worldwide. This disease causes great economic losses to producers, industry and consumers, since there are direct implications in public health due to the zoonotic potential of some agents involved in its etiology and the presence of antimicrobial residues in milk. Considering the multifactorial aspect of the disease and the importance of milk production in family farming, knowledge of the agents involved in its etiology and the susceptibility profiles to antimicrobials is of paramount importance. In this study, the prevalence of Staphylococcus aureus and Streptococcus agalactiae in herds of family farms in the Campo das Vertentes region of Minas Gerais State, and the resistance of these pathogens to the antibiotics most commonly used in the treatment of mastitis in livestock dairy farmers were evaluated. The study involved 200 properties, covering an area of approximately 12,564 km2. The prevalences of pathogens were carried out through microbiological analyzes of milk samples from the bulk milk tank. The modified Baird-Parker Agar medium was used for the detection of S. aureus, and the modified Edwards Agar medium, enriched with 5% desfibrinated sheep blood was used for the detection of S. agalactiae. Disc diffusion technique was used to evaluate resistance to antibiotics. The results showed high prevalence of S. aureus pathogens (71.0%) and S. agalactiae (68.0%) in the farms studied with high levels of resistance and multidrug resistance. The results demonstrate that there are control failures measures to contagious mastitis in studied herds, pointing to the need for more effective control these pathogens and the more judicious use of antibiotics aiming to minimize the problem of resistance to them.